FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Andre Alwi, Linda Santioso (Jurnal Paradigma Akuntansi, 2020)
The purpose of this empirical research is to examine about the effect of firm size, leverage, profitability, liquidity, and growth opportunities on cash holding in manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2017. The research used 66 manufacturing companies that were selected using purposive sampling method for a total of 198 data in three years. Data processed with SPSS version 22.0. The results of this research shows that all independent variables have influence on cash holding simultaneously. The partially test showed that firm size, profitability, and liquidity have positive and significant influence on cash holding, leverage and growth opportunities does not significantly influence cash holding.